Methyl orange (CI acid orange 52) as a new organic semiconductor: Conduction mechanism and dielectrical relaxation - Yahia, I. S.; Abd El-Sadek, M. S.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2012)
The structural, electrical and dielectrical properties of the methyl orange (MO) have been investigated by X-ray diffraction and thermal analysis methods. The electrical conduction and dielectrical relaxation mechanisms of the organic compound at various frequencies and temperatures were analyzed by impedance spectroscopy. The direct current (DC) electrical conductivity confirmed that methyl orange is an organic semiconductor with calculated electronic parameters. The alternating current (AC) electrical conductivity of the sample is controlled by the correlated barrier hopping (CBH) conduction mechanism. The values of the activation energy, the density of states and the binding energy for the alternating current mechanism were determined. The real and imaginary (Z' and Z '') parts of the impedance were found to be a frequency dependence. It was found that Cole-Cole plots of the sample confirm the existence of a temperature-dependent non-Debye relaxation mechanism. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Organic semiconductor; Methyl orange; Impedance spectroscopy; Conduction mechanism; CBH model; Dielectrical relaxation mechanism